Extreme Point Mathematical Programming - Kirby, M. J. L.; Love, H. R.; Swarup, Kanti (Management Science, 1972)
The paper considers a class of optimization problems. The problems are linear programming problems: maximize cx subject to Ax = b with the additional constraint that x must also be an extreme point of a second convex polyhedron Dx = d, x ≧ 0. A cutting-plane algorithm for solving such problems is presented. Two numerical examples are also included.